Model Matematika SEICR Stres Akademik pada Mahasiswa Kimia di Provinsi Aceh - Jelita Jelita; Budi Irwansyah; Lilla Puji Lestari; Faidliyah Nilna Minah; Nuraida Nuraida (Jurnal Penelitian Pendidikan IPA, 2026)
Academic stress among higher education students is a common concern that requires thorough investigation. This study develops and analyzes a SEICR (Susceptible–Exposed–Infected–Confirmed–Recovered) mathematical model to describe academic stress dynamics among chemistry students, treating stress as a contagious phenomenon transmitted through social interactions and peer influence. The model captures the progression of students from susceptibility to stress exposure, active stress, coping intervention, and recovery while incorporating behavioral and institutional factors. A system of nonlinear ordinary differential equations is formulated and analyzed through equilibrium and stability analyses. The basic reproduction number, R₀, is derived using the Next Generation Matrix method and serves as a threshold parameter governing system dynamics. Results indicate that academic stress diminishes and approaches a stress-free equilibrium when R₀ < 1, whereas stress persists and becomes endemic when R₀ > 1. Sensitivity analysis based on the Partial Rank Correlation Coefficient (PRCC) identifies the coping transition rate (δ) as the most influential parameter in reducing stress prevalence, while the transmission rate (β) has a moderate effect. These findings suggest that intervention accessibility plays a greater role than transmission intensity in shaping stress dynamics. Therefore, mitigation strategies should emphasize early detection, timely intervention, and accessible coping support.